Developmental Expression of Mutant PFN1 in Motor Neurons Impacts Neuronal Growth and Motor Performance of Young and Adult Mice - Brettle, Merryn; Stefen, Holly; Djordjevic, Aleksandra; Fok, Sandra Y. Y.; Chan, Josephine W.; van Hummel, Annika; van der Hoven, Julia; Przybyla, Magdalena; Volkerling, Alexander; Ke, Yazi D.; Delerue, Fabien; Ittner, Lars M.; et al. (Frontiers in Molecular Neuroscience, 2019)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease with limited treatment and no cure. Mutations in profilin 1 were identified as a cause of familial ALS in 2012. We investigated the functional impact of mutant profilin 1 expression in spinal cords during mouse development. We developed a novel mouse model with expression of profilin 1 C71G under the control of the Hb9 promoter, targeting expression to α-motor neurons in the spinal cord during development. Embryos of transgenic mice showed evidence of a significant reduction of brachial nerve diameter and a loss of Mendelian inheritance. Despite the lack of transgene expression, adult mice presented with significant motor deficits. Transgenic mice had a significant reduction in the number of motor neurons in the spinal cord. Further analysis of these motor neurons in aged transgenic mice revealed reduced levels of TDP-43 and ChAT expression. Although profilin 1 C71G was only expressed during development, adult mice presented with some ALS-associated pathology and motor symptoms. This study highlights the effect of profilin 1 during neurodevelopment and the impact that this may have in later ALS.